Precision Spectroscopy in Astrophysics: Proceedings of the ESO/Lisbon/Aveiro Conference held in Aveiro, Portugal, 11 - 15 September 2006 - Santos, Nuno C. (Springer-Verlag Berlin Heidelberg, 2008)
High-accuracy Doppler shift measurements and high-precision spectroscopy are primary techniques in the search for exo-planets. Further extremely interesting applications include the analysis of QSO absorption lines to determine the variability of physical constants and the analysis of the isotopic ratios of absorption lines both in stars and in QSOs, and the determination of stellar oscillations through radial velocity measurements. Since the use of high-precision/resolution spectroscopy is closely connected to the ability to collect a large number of photons, the scientific domains using this
Includes bibliographical references
Keywords: Konferenzschrift -- 2006 -- Aveiro; Hochauflösendes Verfahren; Astrospektroskopie